Collagen Microspheres: A Three-Dimensional Culture System for Notochordal Cells. Issue 1 (April 2016) - Yuan, Minting; Yeung, Chiu Wai; Au, Tiffany; Chan, Danny; Cheah, Kathryn S. E.; Chan, Barbara P.
Introduction: The notochord plays a crucial role in the formation and patterning of axial skeleton. Notochordal cells (NCCs) have drawn increasing attentions from developmental biology, stem cells research and tissue engineering in these years as they are important in development and maintenance of NP. However, it is difficult to maintain their survival and phenotype in 2D culture for long term, making it difficult to understand their fate and functional maintenance during intervertebral disc development. This project is to develop a better culture system that is able to maintain the survival and phenotypes of NCCs. Materials and Methods: Foxa2 mNE –Cre/Z/EG heterozygous embryos were developed and NCCs could be identified EGFP signal. NCC isolated with or without FACS-sorting, notochord segments at the anterior, trunk and posterior regions, and whole notochord pulled out from embryo were microencapsulated respectively in type I collagen microspheres and cultured for up to 1 month before characterization for survival and phenotype maintenance. Results: EGFP signal of sorted cells could be maintained after 4 weeks. The EGFP positive cells in collagen microspheres showed colocalization with foxa2 and brachyury, which were considered as markers of NCCs, indicated that they were still NCCs. However, areas with these merged were very rare. EGFP signal of unsorted cells could be maintained and clusters of EGFP positive cells were showed during 4-weeks culture. When the notochord segments were cultured in collagen microspheres, clusters of round EGFP positive cells co-expressing with major NCC markers were found after 1 month, suggesting that NCC phenotype was maintained. Moreover, the number of EGFP positive cells was increased during culture. In the other hand, when the notochord was cultured in collagen microsphere, it started pinching and the pinching region seemed growing at day 28. Conclusion: Type I collagen microspheres present a potential culture system for increasing cell number with EGFP positive signal for at least 4 weeks. NCCs entrapped in type I collagen microspheres could maintained the NCCs phenotype. Comparing with FACS-sorted NCCs, there was increasing number of NCCs in unsorted group, segment culture and whole notochord culture, suggesting that the presence of niche cells, extracellular matrix, and native configuration of notochord may be important to support NCCs growth and phenotype maintenance. Acknowledgments: This work was supported by AoE (AoE/M-04/04), TBRS (T12–708/12-N) and AOSPN (SRN_2011_14). Disclosures : None